Anti-cancer Substances and Safety of Lactic Acid Bacteria in Clinical Treatment - Liu, Chaoran; Zheng, Jiaqi; Ou, Xuan; Han, Yuzhu (Frontiers in Microbiology, 2021)
Lactic acid bacteria (LAB) are a kind of Gram-positive bacteria which can colonize in the biological gastrointestinal tract and play a variety of probiotic roles. LAB have a wide range of applications in industry, animal husbandry, planting, food safety and medical science fields. Previous studies on lactic acid bacteria have typically concentrated on their effects on improving the digestion and absorption of the gastrointestinal tract, regulating the balance of the microflora, and inhibiting the production and accumulation of toxic substances. The resistance of lactic acid bacteria to cancer is a topic of growing interest and relevance. This paper provided a summary of bio-active substances of LAB when they act against cancer, as well as the safety of lactic acid bacteria in clinical cancer treatment. Moreover, this paper further discussed several possible directions for future research and the potential application of LAB as anti-cancer therapy.